Phytochemical Properties, Antioxidant and Antimicrobial Activities, and Colorimetric pH Responsiveness of Rhododendron arboreum Sm. Flower Extract from Manma-Kalikot, Nepal - Shahi, Dikpal Kumar; Achhami, Hari; Karki, Nirmal; Pachhai, Bishwa Babu; Rai, Elina; Gautam, Dinesh; Neupane, Damodar; Regmi, Shukra Raj; Joshi, Rajendra; Bhatt, Lok Ranjan; et al. (Journal of Institute of Science and Technology, 2025)
Rhododendron arboreum Sm. is widely found in the hilly regions of Asia and is recognized as the national flower of Nepal. This study examines the extracts of R. arboreum flowers for total phenolic and flavonoid contents, antioxidant and antimicrobial properties, and pH-responsive color sensing properties. The phenolic content of the extract was assessed using the Folin–Ciocalteu method, flavonoid levels were measured with the aluminum trichloride assay, and antioxidant activity was evaluated through the DPPH radical scavenging test. The antimicrobial properties of the flower extract were evaluated using the agar well diffusion method, while pH responsiveness was examined across the buffer solutions spanning pH 1 to 14. The extract contained total phenolic level of 11±0.15 mg gallic acid equivalent and flavonoid level of 13.36±0.11 mg quercetin equivalent per gram of dry extract. For antioxidant potential, IC50 value was determine which was found to be 20.6±1.18 μg/mL. A strong correlation was observed between phenolic level and antioxidant potential. The extracts showed bactericidal effects against Gram-positive and Gram-negative bacterial strains and moderate antifungal activity. Furthermore, anthocyanin pigments in the extracts displayed notable color variations in buffer solution under different pH conditions. These findings highlight the potential of R. arboreum flowers as a source of natural antioxidants, antimicrobials, and most importantly pH responsive color sensing anthocyanins, encouraging further exploration of their bioactive compounds. This study highlights the untapped potential of R. arboreum, promoting its broader application in scientific research and commercial development.